2022
DOI: 10.3389/fonc.2022.965571
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis of expression and prognostic value of NSUN members in prostate cancer

Abstract: BackgroundProstate cancer is the most common tumor in men worldwide, seriously threatening the health of older men, and 5-methylcytosine (m5C) RNA modification has been shown to have a significant impact on the development and progression of various tumors. However, as the most critical methyltransferase for m5c RNA modification, the role of the NSUN members (NSUN1-7) in prostate cancer is unclear.MethodsWe obtained sequencing data of genes and related clinical data of prostate cancer from The Cancer Genome At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Additionally, 5‐fluorouracil (5‐FU) is the first‐line treatment for colorectal cancer 61 . High NSUN2 expression lowers the sensitivity of fluorouracil in prostate cancer 62 . Further research on combinatorial effects of verteporfin and 5‐FU may help to improve therapeutic efficacy in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 5‐fluorouracil (5‐FU) is the first‐line treatment for colorectal cancer 61 . High NSUN2 expression lowers the sensitivity of fluorouracil in prostate cancer 62 . Further research on combinatorial effects of verteporfin and 5‐FU may help to improve therapeutic efficacy in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to m6A, m5C modifications affect tumour migration and invasion. NOP2 and NSUN2 were found to promote prostate cancer progression by affecting ubiquitin‐mediated genes associated with the p53 signalling pathway, prostate cancer proteolysis and RNA degradation 87 . Furthermore, it was found that NSUN2 could regulate the m5C modification of the oncogene FOXC2‐AS1 and make it bind to YBX1 during GC progression 88 .…”
Section: The Emerging Roles Of Rna Methylation As Critical Regulators...mentioning
confidence: 99%
“…Similar to m 6 A modification, m 5 C RNA methylation is also required for the regulation of the immune microenvironment in diverse cancer types. Increasing evidence has identified multiple m 5 C RNA regulators are abnormally expressed in many cancer tissues and play important roles in modulating immune functions in cancer 474–477 . In triple‐negative BC, NSUN2 has been found to be expressed in monocytes/macrophages and NSUN6, on the other hand, is expressed in Treg cells 478 .…”
Section: Association Of Rna Methylation With Cancer Immunitymentioning
confidence: 99%